Mechanical properties of oil palm fruit bunch (OPFB) fiber composite / Izwan Amir - Amir, Izwan (2005)
This project required the studies on the natural fiber composite material which is the oil palm fruit bunch as a fiber component. By conducting through several experiments, the data will be collected to determine the mechanical properties of the material. Mechanical properties from the study will be compared with the previous natural fiber composite. Hence, this material should give possible practice for engineering applications.